ABOUT THE DIGITAL RESTORATION OF HISTORICAL TEXT DOCUMENTS - V. V. Starovoitov (Системный анализ и прикладная информатика, 2015)
The main problems of old text document restoration and approaches to their solution during restoration of images of these documents by methods of information technology are considered. Primary source documents are not changed, but their digital copies can be modified with orientation on different applications and according to the different levels of processing